A post-mortem of austerity: the Greek experience - Alexiou, Constantinos; Nellis, Joseph G. (Economic Issues Foundation Fund, 2016)
The policies of economic austerity are invoked whenever a country's public deficit is spiralling out of control. Given the intricate channels through which deficits and debt can be financed, i.e. either through borrowing or money creation, manipulation of public deficits may pose significant constraints on economic growth, social cohesion and political stability. In this context, austerity is a policy expedient that, if applied irresponsibly, might have irreversible effects on both economic and social structures. In Greece economic policies of austerity, in conjunction with internal devaluation, have been adopted in an attempt to improve competitiveness, correct external deficits and promote export-led growth. In this paper, by scrutinising a range of key economic indicators, we argue that austerity has depressed significantly the real economy in Greece, threatening further an already crippled economic environment with a danger of further stagnation. We also provide econometric evidence for the period 2000 - 2013 which shows that the positive contribution of net exports to economic growth in Greece has been as a result of relatively low domestic demand, not to relative gains in the international price competitiveness of Greek enterprises. Finally, it is envisaged that the lack of adequate endogenous capacity as a means of galvanising economic growth has the potential to usher in prolonged periods of economic depression.